Roles of budgetary participation on leader's performance: a study case in Ternate - Hashim, Abd. Wahab; Imam Hanafi; Fitrianto, Anwar; Darwish, Herman (Canadian Center of Science and Education, 2014)
This study aims to analyze the relationship between budgetary participation with leadership performance. The population of this study was under the leadership of mid-level and intermediate level on SKPD (Regional Work Unit) Ternate. Random sampling techniques use proportional sampling and analytical methods used are factor analysis. The research proves that the higher the participation in the preparation of the budget will further improve the performance of the leadership. Meanwhile, budget goal commitment does not affect the relationship between budgetary participation with leadership performance, this is because the possible existence of distrust to achieve budget targets.